Comparative analysis of glycaemic index, antioxidant capacity, viscosity, and nutritional composition of hospital-made and commercial blenderized tube feeding for Type 2 Diabetes Mellitus - Rujiraporn Glankhetkit; Waraporn Phanprom; Chutikan Sakphisutthikul (International Journal of Public Health Asia Pacific, 2026)
Background: Hospital-prepared blenderized tube feeding diets (BDs) are widely used for people with type 2 diabetes mellitus (T2DM) in Thailand, but their glycaemic performance, antioxidant capacity and physicochemical safety remain unclear. Objectives: This study aimed to compare five formulas for glycaemic performance, antioxidant capacity, physicochemical safety, and nutritional composition. Methods: Five formulas were tested: one general blenderized diet (Control), three hospital-made diabetes-specific BDs (Hospital A, B, and C), and one commercial diabetes-specific enteral formula. Apparent viscosity was measured using a rotational viscometer. Nutrient composition was analysed using INMUCAL-Nutrients software based on the Thai Food Composition Database. Antioxidant capacity was determined by total phenolic content (TPC), total flavonoid content (TFC) and DPPH radical scavenging (IC50). In vitro glycaemic index was estimated using the Goñi enzymatic starch hydrolysis method. Results: Apparent viscosity was 16.60-164.00mPa·s, below the safety threshold (